Neuropsychological profile in Italian children with neurofibromatosis type 1 (NF1) and their relationships with neuroradiological data: Preliminary results. (September 2018) - Parmeggiani, A.; Boiani, F.; Capponi, S.; Duca, M.; Angotti, M.; Pignataro, V.; Sacrato, L.; Spinardi, L.; Vara, G.; Maltoni, L.; Cecconi, I.; Pastore Trossello, M.; et al.
Abstract: Background: Neurofibromatosis type 1 is a genetic disorder associated with cognitive deficits, learning disabilities and behavioral problems. These domains appear to have a still controversial debated association with local areas of T2-hyperintensities on MRI images, called unidentified bright objects (UBOs). Methods: A cohort of 36 children (aged 7–11 years) included consecutively, underwent neuropsychological and behavioral assessment to determine their cognitive and neuropsychological profile, and the frequency of specific learning disabilities. MRI examination was used to determine the impact of UBOs' presence, number, and location on the cognitive, neuropsychological and behavioral profile, and also the presence of optic glioma. Results: The mean full intelligence quotient was 104.6; only one child had mild intellectual disability. Forty one percent of children had a diagnosis of specific learning disabilities and reading was mainly involved. Twenty per cent had attention problems. All children had normal scores in visuo-motor and visuo-perceptual tests. UBOs were present in 94.0% of the MRI examinations. Two children had optic glioma. Children with UBOs in a specific location and children with UBOs elsewhere were statistically compared, no one of the location seemed to have an impact on general cognition measured with full intelligence quotient. The thalamus was associated with problems in calculation and striatum with behavioral problems. An inverse relationship between the number of UBOs and the full intelligence quotient was present, but without a statistical significance. Conclusions: In this study, the specific location of UBOs did not seem to influence the general cognitive profile and also the relationship between their number and the full intelligence quotient was not significant; these results are still controversial in literature. Finally, the presence of UBOs in the thalamus and striatum may represent a neuroradiological pattern that influences performances in calculation and behavior respectively in children with Neurofibromatosis type 1. Highlights: Children with neurofibromatosis type 1 have a normal cognitive function and high frequency of Learning Disabilities. Attention deficits are manly involved in neuropsychological test and visuo-motor tasks aren't compromised in all children. Parent's reported especially attention and/or hyperactivity and internalizing problems. UBOs are present in most of children and their number did not seem to have a relationship with full intelligence quotient. The distribution of UBOs in thalamus and striatum may influence calculation skills and behavioral profile respectively.